Application of Array-based Comparative Genome Hybridization in Children with Developmental Delay or Mental Retardation - Jao-Shwann Liang; Keiko Shimojima; Toshiyuki Yamamoto (Elsevier, 2008)
Children with developmental delay or mental retardation (DD/MR) are commonly en countered in child neurology clinics, and establishing an etiologic diagnosis is a challenge for child neurologists. Among the etiologies, chromosomal imbalance is one of the most important causes. However, many of these chromosomal imbalances are submicroscopic and cannot be detected by conventional cytogenetic methods. Microarray-based comparative genomic hybridization (array CGH) is considered to be superior in the investigation of chromosomal deletions or duplications in children with DD/MR, and has been demonstrated to improve the diagnostic detection rate for these small chromosomal abnormalities. Here, we review the recent studies of array CGH in the evaluation of patients with idiopathic DD/MR.